The choice of whether to participate in a phase I clinical trial: increasing the awareness of patients with cancer. An exploratory study. Issue 3 (10th October 2013) - Catania, C.; Radice, D.; Spitaleri, G.; Adamoli, L.; Noberasco, C.; Delmonte, A.; Vecchio, F.; de, F.; Toffalorio, F.; Goldhirsch, A.; De Pas, T.
Abstract Objective In a previous study, we found that patients who were offered the possibility of participation in a clinical trial had unexpressed concerns and fears that prevented them from making free or fully knowledgeable choices about their trial participation. In a selected population of patients who were offered participation in a phase I trial, we prospectively investigated whether a face‐to‐face discussion about their unexpressed fears might lead to a more conscious decision about whether to accept/refuse participation in the trial. Methods After the presentation of the trial, a questionnaire was administered to assess the presence of specific fears. Before the patients decided whether to participate in the trial, they discussed any fears that they had; finally, the impact of the discussion on the patients' choice to participate was evaluated. Results The majority (86%) of the patients thought that physicians conduct clinical trials for scientific interest, 13% felt exploited as 'guinea pigs' and 20% believed they were offered participation because they had no further hope for improvement. These existing fears were not elicited during the trial interview because the patients were themselves unaware of having them (28%) and because of fear of the doctors (3%). The possibility of discussing these fears was felt as an opportunity and made patients feel more conscious (92%) and freer (97%) when making their choice. Conclusions Recognising and discussing misconceptions and fears, often unexpressed, make patients freer and more aware when facing the choice of whether or not → participate in a phase I clinical trial. Copyright © 2013 John Wiley & Sons, Ltd.